The coronavirus (COVID‐19) pandemic's impact on mental health - Bilal Javed; Abdullah Sarwer; Erik B. Soto; Zia‐ur‐Rehman Mashwani (2020)
Abstract Throughout the world, the public is being informed about the physical effects of SARS‐CoV‐2 infection and steps to take to prevent exposure to the coronavirus and manage symptoms of COVID‐19 if they appear. However, the effects of this pandemic on one's mental health have not been studied at length and are still not known. As all efforts are focused on understanding the epidemiology, clinical features, transmission patterns, and management of the COVID‐19 outbreak, there has been very little concern expressed over the effects on one's mental health and on strategies to prevent stigmatization. People's behavior may greatly affect the pandemic's dynamic by altering the severity, transmission, disease flow, and repercussions. The present situation requires raising awareness in public, which can be helpful to deal with this calamity. This perspective article provides a detailed overview of the effects of the COVID‐19 outbreak on the mental health of people.